ANALISIS STRATEGI KOMUNIKASI PEMASARAN PT. INDONESIA VILLAJAYA DALAM UPAYA MEMBANGUN LOYALITAS PELANGGAN - Dessy Kurniawanti; Bambang Hendrawan (Politeknik Negeri Batam, 2017)
This study aims to analyze how the process of marketing communication strategies such as: advertising, sales promotion, public relations and publicity, personal selling, and direct marketing conducted by PT. Indonesia Villajaya. The research data was obtained through direct observation, documentation, as well as in-depth interviews with five informants. This research method using descriptive qualitative method. Analysis of the data include: data collection, data reduction, data presentation, and conclusion. The results showed that PT. Indonesia Villajaya conduct marketing communication strategy with reference to the integrated marketing communications strategy with process include: advertising, sales promotion, direct marketing, personal selling, and community relations & publicity. With the process of the strategy undertaken during this helps in increasing the public's brand awareness, enhance brand image and increase sales for the company